Periglacial-Geomorphological Investigations at Resolute, 1959 - Cook, Frank A. (ARCTIC, 1960)
In 1959 the Geographical Branch of the Department of Mines and Technical Surveys instituted a long-term program of research in the area at Resolute, Cornwallis Island, N.W.T., into problems of periglacial geomorphology, a relatively new branch of study relating to certain soil and landform features produced in very cold climates. This note is a progress report on the field work of the first year carried out by the writer, assisted by Jacek Romanowski, a graduate of McGill University, Montreal. The area was chosen as the site of investigations because it lies in an active periglacial region. Vegetation is almost absent, and the mechanical actions of frost are reduced to as simple a process as can be found in nature. On the large areas of barren land many periglacial features are revealed with remarkable perfection, especially types of patterned ground. Furthermore, Resolute is easily accessible by air; scheduled flights and many unscheduled flights offer opportunity for transport of personnel and equipment. The annual resupply by boat permits movement of large equipment into the area. Limited workshop and laboratory facilities are available for repair of equipment, sharpening of tools, etc., an important factor in permafrost work. The presence of a first-class meteorological station provides complete meteorological data, indispensable in the study of periglacial processes and phenomena. .